The processivity of DNA synthesis exhibited by drug-resistant variants of human immunodeficiency virus type-1 reverse transcriptase. - Avidan, O (1998)
The reverse transcriptase (RT) of human immunodeficiency virus (HIV) undergoes rapid mutagenesis due to selective pressure by RT inhibitors which renders the mutated RT variants resistant to these inhibitors. Resistance to nucleoside analogs during drug therapy results from point mutations that lead to specific variations in the RT sequences. It was recently shown that several well-defined drug-resistant variants of HIV-1 RT (i.e. Leu74Val, Glu89Gly, Tyr183Phe, Met184Lue, Met184Val and Met184Ile) show enhanced accuracy of DNA synthesis relative to wild-type HIV-1 RT (as evident from a reduction in the capacity to introduce mispairs and to elongate them). Since the last two Met184 variants were shown also to possess decreased processivity of DNA synthesis, it was recently suggested that there might be an inverse correlation between the apparent in vitro fidelity and processivity of DNA synthesis in drug-resistant HIV-1 RT mutants. In the present study we have conducted a comparative analysis of the processivity of DNA synthesis on both DNA and RNA templates of the Leu74Val, Glu89Gly, Tyr183Phe and Met184Leu drug-resistant mutants of HIV-1 RT in comparison with wild-type RT. Apart from the Met184 mutant, which shows reduced relative processivity (similar to the other mutants of residue 184 already studied), the other three variants have relative processivity at least as high as that of wild-type RT. This suggests that the inverse correlation between reduced processivity and increased fidelity is restricted only to mutants with modifications of Met184. The results presented may bear on potential mechanistic and structural differences in the involvement of the various mutated residues studied in processivity, fidelity and sensitivity to nucleoside analogs.